Editorials: Leading Education in Times of Crisis: Perils or Opportunities? - Abukari, Abdulai (2021)
Papers in this special issue of the Journal for Researching Education Practice and Theory (JREPT) is based on selected papers from the virtual conference on ‘Leading Education in Times of Crisis’ hosted by the Faculty of Education at the British University in Dubai on 29th May 2021. Since the beginning of the COVID-19 pandemic over two years ago, leaders across the globe have grappled to respond to the emergencies. Workable leadership practices, familiar models and theories and ‘comfort zones’ have been tested and stretched beyond their limits resulting in redefining what effective leadership is. Emergencies such as the pandemic bring unpredictable challenges, put leadership approaches to the test at all levels/sectors and force leaders to rethink and redefine their leadership approaches in order to adapt to the new realities (Dumulescu & Mutiu, 2021; Bagwell, 2020). At all levels of the education sector, leadership is considered as a crucial aspect to determine quality and success; more so, effectively lead in disruptive times. It is argued that most leaders in education have limited or no training in ‘crisis leadership’ or have very limited experience dealing with crisis of such magnitude as the pandemic (Mutch, 2015; McLeod & Dulsky, 2021). However, going by the view that in a school situation ‘crisis can be regarded as any urgent situation that requires the school leader to take fast and decisive action’, school leaders daily routines are often confronted with such ‘urgent situations’ (Smith & Riley, 1 © 2021 Journal for Researching Education Practice and Theory Abdulai Abukari and Solomon Arulraj David 2012, 58) although, at a much lesser degree or scale (Smith & Riley, 2012). Whitla (2003) provides examples of school-based crisis such as a number of students killed in a motto accident and a teacher committing suicide in school. Smith and Riley (2012, 57) describe crisis leadership in education as leadership in times of crisis that focuses on “dealing with events, emotions and consequences in the immediate present in ways that minimise personal and organisational harm to the school and school community”. Nonetheless, the facts still remain that the pandemic presented an extremely challenging situation for school leaders that had influencing factors from beyond the school community. In the face of this unprecedented crisis, what are the challenges and opportunities for school leaders and what leadership model/s could leaders rely on to effectively lead in unprecedented crisis situations to minimise consequences?